Trial effectiveness of daily and flexible administration of micronutrient sprinkles to control anaemia in young children in rural Bangladesh - Haseen, Farhana; Hyder, Ziauddin; Ip, Hedy; Rahman, Mizanur; Zlotkin, Stanley (BRAC Research and Evaluation Division (RED), 2019)
Iron deficiency-anaemia is a major public health problem worldwide, especially in developing countries. Infants and young children aged between 6-24 months are one of the most vulnerable groups. Although iron intervention programme, such as iron-folate tablets, have been implemented for pregnant women at the national level in many countries, a suitable effective public health strategy to control childhood anaemia remains to be established. In response to this need, researchers at the Hospital for Sick Children and the University of Toronto in Canada developed "Sprinkles", an innovative 'home-fortification' strategy. Sprinkles consist of microencapsulated iron (as ferrous fumarate) and other essential micronutrients in powder fonn that are packed into single serve sachets, which are to be mixed into any kind of weaning food right before serving. The efficacy of Sprinkles in improving anaemia status of young children has been tested in several countries around the world. A previous efficacy trial in Bangladesh, testing daily and weekly administration of Sprinkles, revealed in focus group discussions that caregivers preferred more flexible instructions for Sprinkles use. Therefore, in this study, the flexible administration of Sprinkles was examined on the basis that it may increase programme effectiveness by improving adherence.